PENGEMBANGAN KARIR PERAWAT TERHADAP PENINGKATAN MUTU PELAYANAN KEPERAWATAN PROFESIONAL DI RUANG RAWAT ANAK RSUP. Dr. M. DJAMIL PADANG - , Neila Sulung ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Nurse is one of the health professions in the health world. As a profession it is obviously expected that the nurse must give professional service, so that the nurse should have the competence to meet the standard of nursing practice. It is also expected in the future professional nurse performance can give positive contribution onto the quality of nursing care and nurse career development. Therefore, the research is aimed at finding out the influence of child nurse career development on the improvement of the quality of professional nursing service in RSUP Dr. M. Djamil, Padang, West Sumatera. Action research is used in this research, which took place since May to September in 2012. The research subject is nurses who work in child room, pediatric surgery, and child intensive care unit amounted 75 people with DIII and S1 nursing educational background. Before the research was carried out, the participants from the head of nursing section, nursing committee, education and training section, and the head of the room were provided with a preceptor and mentor training. Then, socialization was done before conducting intervention of child nurse competence to the subject of research. The data was collected by using the motivation questionnaire, human resource management questionnaire, child nurse competence, as well as patient satisfaction. The characteristic of the research subject was selected based on education, training, work experience and age. Path analysis is used to analyze data. The result of research shows that the nurse with D III nurse education amounted 93% and 7%, never participate in training in the last 3 years is 53%, age range 20-30 years is 51%. The nurse that has the most work experience of less than 5 years is 57%, permanent employee force type is 68%, and level category of clinical nurse career (PK) is 1of 30 people, PK2 is 15 people, PK3 is 25 people, and PK4 is 5 people. In this research the variables influence the nursing career are education, motivation, and management and the value is (p = 0.009). Meanwhile, variables which do not influence the nurse career are age, training, work experience with the value (p > 0:20). On the other hand, the variable that has significantly influenced on the nursing service quality is only education (p = 0.039) and nurse career development is (P = 0.000). When the interventions are given twice, there has been an increase of nurse competence on each career level with the average 2.65. It can concluded from the research that competence intervention that has been carried out in child care room RSUP Dr. M. Djamil can increase nurse competence and nurse career as well as the quality of service care nursing.